Pepper mild mottle virus: Agricultural menace turned effective tool for microbial water quality monitoring and assessing (waste)water treatment technologies - Symonds, Erin M.; Rosario, Karyna; Breitbart, Mya (PLoS pathogens, 2019)
About the Authors: Erin M. Symonds * E-mail: esymonds@mail.usf.edu Affiliation: College of Marine Science, University of South Florida, Saint Petersburg, Florida, United States of America ORCID logo http://orcid.org/0000-0003-0506-2510 Karyna Rosario Affiliation: College of Marine Science, University of South Florida, Saint Petersburg, Florida, United States of America ORCID logo http://orcid.org/0000-0001-9847-4113 Mya Breitbart Affiliation: College of Marine Science, University of South Florida, Saint Petersburg, Florida, United States of America ORCID logo http://orcid.org/0000-0003-3210-2899 Introduction Domestic wastewater pollution in environmental waters or water reuse supplies represents a threat to public health because of high concentrations of diverse pathogens associated with human excreta [1]. Since it is difficult to directly measure waterborne pathogens of concern, microbial water quality monitoring efforts often use surrogates or indicator organisms that are easily detected and whose presence reflects pathogen persistence [2]. [...]enteric viruses are typically found in low concentrations (<105 copies per liter) in domestic wastewater in the absence of an outbreak [16] and further diluted upon discharge to environmental waters, which hinders their detection [14, 15]. Because viral enteric pathogens are not practical indicators of fecal pollution, viruses infecting gut bacteria have also been investigated. Notably, PMMoV was most often detected along with human pathogens in waters exposed to untreated domestic wastewater and least often in the absence of known pollution sources (11.4% PMMoV-positive samples, with 0% pathogen co-occurrence). [...]PMMoV seems to be a conservative tracer, but its detection and concentration correlate with the presence of human enteric pathogens in environmental waters exposed to wastewater contamination. In addition to having practical applications for measuring virus reduction at the full-scale treatment facilities, PMMoV is also useful for quantifying virus reductions by innovative water treatment technologies at smaller scales (summarized in [4]) as well as point-of-use household drinking water treatment [32] and on-farm riverbank filtration systems [33]. Because PMMoV is currently quantified using molecular methods that cannot determine virus infectivity, the incorporation of culture-based analyses (which would require plant growth chambers) [8] and/or selective pretreatment for infectious particles could improve future virus reduction analyses to assess treatment efficiency [34].